AB1170 Prevalence of anti-carp antibodies in patients with primary sjÖgren's syndrome: association with clinical, serological and histological aspects. (15th June 2017) - Colafrancesco, S; Piacarelli, G; Pecani, A; Colasanti, T; Spinelli, F; Alessandri, C; Barbati, C; Vomero, M; Cerbelli, B; Priori, R; Valesini, G
Abstract : Background: The presence of antibodies against carbamylated peptides (anti-CarP) has been associated with increased disease activity and severe joint damage in rheumatoid arthritis. Our group has demonstrated their presence also in other inflammatory conditions with a high prevalence in Sjogren's Syndrome (SS) (14/45, 31.1%) 1 . There is only one study up to now investigating anti-CarP in SS demonstrating a prevalence of these antibodies in 27% of cases and an association with the presence of germinal centres (GCs) 2 . Thus, these antibodies have been proposed as a new tool for identifying SS patients with a more aggressive disease. Objectives: To confirm the presence of anti-CarP antibodies in a large monocentric cohort of patients with SS and investigate their association with clinical, serological and histological features. Methods: Serum samples from consecutive patients with SS (AECC criteria) were collected and stored at -20°. Anti-CarP antibodies were detected by a modified solid-phase "home-made" ELISA 1 . The mean +3 times SD was used as cut-off. Minor paraffin embedded salivary glands were stained by H&E and IHC using lymphocytes T and B markers [anti-CD3, anti-CD20 (DAKO)]. GCs presence was defined by H&E and confirmed by identification of follicular dendritic cells (anti-CD21, DAKO). Images were analysed as follows: focus score (FS) calculation, mean foci area, presence of segregated foci (SF), GCs and lymphoepithelial lesions (LELs). Results: Clinical and laboratory features of SS patients are shown in table. Serum anti-CarP were detected in 30/104 patients (28.8%) without association with any clinical or serological feature (Fisher's exact test). Positive patients were more likely to present SF (P=0.024). No association was found with the presence of GCs or LELs. Anti-CarP titre correlated with the FS (P=0.045, r=0.304), the number of foci (P=0.008, r=0.347), mean foci area (P=0.028, r=) and the percentage of SF (P=0.046, r=0.331) (Spearman's test). Prevalence of anti-CarP was higher in patients with arthritis [7/15 (46.6%)] than those without ([23/89 (25.8%)] (p>0.05). Mean anti-CarP titre was higher in patients with arthritis compared to those without (322.3±173.8 aU/ml vs 279.5±171.1, P=0.004, respectively). Conclusions: This is the largest cohort of SS patients screened for anti-CarP so far. Our results show a prevalence of anti-Carp antibodies in agreement with the literature; however, no association was found with any clinical or serological aspect. Anti-CarP do not seem to be associated with histological features predictive of lymphoma, i.e. CGs and LELs. Nonetheless, considering the titre correlation with the FS, mean foci area and percentage of segregation, higher serum levels of anti-CarP may reflect a severe tissue inflammation more prone to form organized infiltrates. This finding, in association with the evidence of higher levels in patients with arthritis, may support the idea that these antibodies are useful to measure the severity of systemic inflammation. References: Pecani A et al. Arthritis Res Ther. 2016 25;18(1):276. Bergum B et al. Ann Rheum Dis. 2016;75(8):1494–500. Disclosure of Interest: None declared